Комплексні геофізичні дослідження зсувонебезпечної ділянки на території МДЦ "Артек" (АР Крим) - Туманов, В.В.; Савченко, А.В.; Богак, М.Ю.; Юфа, Я.М.; Костюченко, О.Л.; Федін, М.М. (Наукові праці УкрНДМІ НАН України, 2012)
Установлены особенности распространения геофизических полей по данным ЕИЭМПЗ, сейсмо- и электроразведочных методов на оползнеопасной территории, прилегающей к стадиону МДЦ "Артек". Features related to propagation of geophysical fields according to the Earth’s natural pulsed electromagnetic field data, seismic exploration and geoelectric prospecting methods at landslide-hazardous area adjacent to the stadium belonging to the International Children Center "Artek" are defined.